Evaluation In Districts Kotagede Yogyakarta In Give Service With Based Human Resources - Damar Panji Adikumoro; Ismi Dwi Astuti Nurhaeni Ismi Dwi Astuti Nurhaeni; Rino A. Nugroho Rino A. Nugroho (Journal Of Social Science (JoSS), 2023)
This study aims to determine evaluation related to work ability, motivation, quality and quantity of work of state civil servants in Kotagede District in providing services based on human resources. This study uses a qualitative method. The research informants were 5 people, the data sources consisted of primary and secondary data obtained from data collection techniques by observing and interviewing. The results of the study show that the application of ASN Performance Evaluation in improving the performance of the state civil apparatus in Kotagede District is quite good and systematic. This is supported by the cooperation of various parties. In addition, the implementation of the performance carried out in the Kotagede District has experienced a very significant increase, this is because the attention from the Kotagede District is quite extraordinary. One form of concern is by sending several state civil servants to attend training and technical guidance regarding SOPs and involve them in the preparation of SOPs.